2017
DOI: 10.1002/uog.17373
|View full text |Cite
|
Sign up to set email alerts
|

sFlt‐1/PlGF for prediction of early‐onset pre‐eclampsia: STEPS (Study of Early Pre‐eclampsia in Spain)

Abstract: ObjectiveA high ratio of soluble fms‐like tyrosine kinase‐1 (sFlt‐1) to placental growth factor (PlGF) has been linked to pre‐eclampsia (PE). We evaluated the sFlt‐1/PlGF ratio as a predictive marker for early‐onset PE in women at risk of PE.MethodsThis prospective, Spanish, multicenter study included pregnant women with a risk factor for PE, including intrauterine growth restriction, PE, eclampsia or hemolysis, elevated liver enzymes and low platelet count syndrome in previous pregnancy, pregestational diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 56 publications
5
34
1
Order By: Relevance
“…The onset of hypertension during pregnancy or worsening of pre-existing chronic hypertension without proteinuria represents a complex situation, in which it is essential to rule out PE. Verlohren et al [ 17 ] showed that the sFlt-1/PlGF ratio in patients with PE is significantly higher compared with that in patients with chronic and gestational hypertension. These data, recently confirmed in a Spanish cohort [ 17 ], demonstrated the role of the sFlt-1/PlGF ratio in differentiating PE and other pregnancy-related hypertensive disorders [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset of hypertension during pregnancy or worsening of pre-existing chronic hypertension without proteinuria represents a complex situation, in which it is essential to rule out PE. Verlohren et al [ 17 ] showed that the sFlt-1/PlGF ratio in patients with PE is significantly higher compared with that in patients with chronic and gestational hypertension. These data, recently confirmed in a Spanish cohort [ 17 ], demonstrated the role of the sFlt-1/PlGF ratio in differentiating PE and other pregnancy-related hypertensive disorders [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include placental growth factor (PlGF), soluble vascular endothelial growth factor receptor 1, endoglin, and their ratios [55,58,65,82,109,113117]. Prediction models have also been developed that combine maternal blood pressure, uterine artery Doppler, PlGF [99,101,118124], pregnancy-associated plasma protein A, and inhibin-A [125].…”
Section: Introductionmentioning
confidence: 99%
“…al, in their study using the same ratio found that 19.64% developed preeclampsia. 12 They also reported that 35.5% study participants with history of preeclampsia in previous pregnancy developed early onset preeclampsia. These results differ from that of the current study, where 48.6% had early onset preeclampsia.…”
Section: Sensitivity Specificitymentioning
confidence: 96%
“…While in a similar study conducted by Perales A et al, found that sFlt-1/Plgf ratio was better predictor for preeclampsia than uterine artery doppler pulsatility index with sensitivity and specificity of 91.1% and 82% respectively similar to our study. 12 Taraseviciene V et al in the study on prediction of preeclampsia found that sensitivity and specificity of sFlt-1/Plgf was 95.8% and 96.2% respectively. 14…”
Section: Sensitivity Specificitymentioning
confidence: 97%